Determination of pesticide residues in globe artichoke leaves and fruits by GC–MS and LC–MS/MS using the same QuEChERS procedure. (15th July 2017) - Machado, Ignacio; Gérez, Natalia; Pistón, Mariela; Heinzen, Horacio; Cesio, María Verónica
Highlights: Pesticides residues in artichoke fruits and leaves can be determined using the same modified QuEChERS method. The method was selected among three adapted for these particular matrices. Although both matrices showed similar chemical composition, artichoke leaves co-extractives caused higher matrix effects. The validated method was successfully applied for the analysis of real samples. Abstract: Aiming to select the most suitable sample preparation for the multiresidue analysis of pesticides in globe artichoke ( Cynara cardunculus L.), a modified QuEChERS, a matrix solid phase dispersion and a dispersive ethyl acetate extraction were compared. Trueness and precision were determined at 0.2 mg kg −1 for the three methods. The modified QuEChERS showed the best performance. The scope of the method was enlarged to 35 GC and 63 LC amenable pesticides, its overall performance was evaluated and validated to artichoke leaves and fruits according to DG-SANTE Guidelines. Different matrix effects were observed for most of the pesticides which were higher for leaves than fruits. Difenoconazole and flutriafol suffered signal suppression in leaves extracts but showed positive matrix effects in fruits. All pesticides were analyzed at or below their Maximum Residue Levels fixed for globe artichoke by the European Union. The method was successfully applied for the analysis of commercial samples.